Tebang Pilih Mengubah Keanekaragaman Semut Tanah Hutan di Kalimantan Timur, Indonesia - Ahmad Budiaman; Noor Farikhah Haneda; Laela Nurahma (Jurnal Ilmu Pertanian Indonesia, 2021)
This study assesses the short-term effects of selective cutting on the diversity of ground ants (Hymenoptera: Formicidae) in the secondary rainforest. Ground ants were collected using a pitfall trap in a circular sample plot of 0.5 ha. A total of nine sample plots were randomly placed in a 98-ha cutting compartment. Fifteen pitfall traps were planted in each circular plot. A total of 135 pitfall traps were established in the cutting compartment. The average cutting intensity of 8 trees/haas applied in the cutting compartment. Insect sampling and measurement of environmental factors were carried before cutting and two days after cutting. In this study, the abundance, diversity, species richness, and evenness index of ground ants before cutting compared to after cutting. The results of this study indicated that the short-term impact of selective cutting on ground ants was varied. Selective cutting may increase or decrease the abundance and morphospecies composition of ground ants. The abundance of forager and ground-dwelling omnivores increased after selective cutting, whereas for the predator, scavenger, and seed disperser ants were decreased after selective cutting. Keywords: biodiversity, forest conservation, ground ant, selective cutting